2001
DOI: 10.1159/000046847
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Plasticity in Cochlear Implant Patients

Abstract: Auditory re-afferentation by cochlear implants (CI) offers a unique opportunity to study directly from within the auditory modality plastic changes taking place at organisational levels up to the supra- or polymodal level. These plastic changes resulting from deafness and chronic electrical stimulation can be studied using modern neuroimaging techniques. In this paper, we review the available techniques and the experimental approaches to human studies of plasticity, we discuss the different forms of plasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 53 publications
9
67
0
8
Order By: Relevance
“…Using PET, we were able to study plasticity related to implantation as focal alterations of the functional specialization of speech areas and as modifications at the level of large-scale neural circuits, revealing a particular form of cross-modal interaction (see review by Giraud et al [2001c]). …”
Section: Cochlear Implantsmentioning
confidence: 99%
“…Using PET, we were able to study plasticity related to implantation as focal alterations of the functional specialization of speech areas and as modifications at the level of large-scale neural circuits, revealing a particular form of cross-modal interaction (see review by Giraud et al [2001c]). …”
Section: Cochlear Implantsmentioning
confidence: 99%
“…It may be that dependence on visual information and cross-modal plasticity, which favors visual information processing, have a negative effect on auditory information processing after implantation. In order to successfully perceive auditory speech, integration of audiovisual inputs is known to be crucial [10,11] . However, it seems that too much dependence on visual information before CI acts as an impediment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined brain activity using 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) imaging to reveal this difference in brain plasticity. They showed that the cortices of individuals with cochlear implants who achieve successful levels of speech perception activate more areas than in those with normal hearing when listening to speech stimuli [10,11] . PET studies also show that the right secondary auditory and auditory association cortices are significantly activated in response to words, prose [12] , and…”
Section: Introductionmentioning
confidence: 99%
“…8,13,19,24 Buna karşın bazı çalışmalarda ise MRG'nin implanta herhangi bir zarar vermediği belirtilmektedir. [52][53][54][55][56] Böyle bir durum karşısında kohlear implant cerrahisi geçiren hastanın implantı takan cerraha danışması uygun olacaktır. 8 Kohlear implantın dış parçasının sudan sakınılması gerektiği konusunda hasta ve yakınları bilgilendirilir.…”
Section: Taburculuk Eği̇ti̇mi̇unclassified